Challenges faced by G1 contractors / Fatin Nabilah Imam and Mohd Esham Mamat - Imam, Fatin Nabilah; Mamat, Mohd Esham (2019)
Nowadays, the number of contractors involved in construction industry is increasingly. The data obtained from Construction Industry Development Board Malaysia (CIDB) of contractor registered especially G1 contractor more than fifty thousand. However, the domination and performance of Bumiputra small firms involved in the construction sector still lagging compared to non-Bumiputra firms The aim of this paper is to identify the challenges faced by G1 contractor in construction industry. The objective of this study is to identify the challenges faced by G1 contractor in construction industry. By using questionnaire, this paper offer and recommend the solution and idea to identify the challenges faced by G1 contractor in construction industry. The results founds that there are different solution to overcome the challenges. Future research should include a larger sample size such as across peninsular Malaysia.